2010
DOI: 10.1007/s11274-010-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization and expression analysis of a pacC homolog in the mycoparasite Coniothyrium minitans

Abstract: Coniothyrium minitans is a mycoparasite and a promising biocontrol agent of Sclerotinia sclerotiorum, an omniovorous plant pathogenic fungus. Our previous studies indicate that mycoparasitism and antibiosis of C. minitans are greatly affected by ambient pH, implying that a pH-regulatory system may exist in C. minitans. In this study, we cloned a putative pH-responsive transcription factor gene, cmpacC, from strain Chy-1 of C. minitans. The full-length DNA sequence of cmpacC (GenBank Acc. No. FJ176399) has one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Oxalic acid, a pathogenicity factor of S. sclerotiorum, is likely to be a signal for this interaction. C. minitans produces antifungal substances with increasing activity at low pH caused by oxalic acid and produces beta-1,3-glucanase, an fCWDE, at higher pH after oxalic acid is degraded (15)(16)(17). Theoretically, the interactions between C. minitans and S. sclerotiorum are similar to that between the plant pathogen and host plants, and many similar pathways are likely to be involved in this hyperparasitism.…”
mentioning
confidence: 99%
“…Oxalic acid, a pathogenicity factor of S. sclerotiorum, is likely to be a signal for this interaction. C. minitans produces antifungal substances with increasing activity at low pH caused by oxalic acid and produces beta-1,3-glucanase, an fCWDE, at higher pH after oxalic acid is degraded (15)(16)(17). Theoretically, the interactions between C. minitans and S. sclerotiorum are similar to that between the plant pathogen and host plants, and many similar pathways are likely to be involved in this hyperparasitism.…”
mentioning
confidence: 99%
“…The mechanism is that the activated PacC induces transcription of fungal genes preferentially expressed under alkaline conditions and simultaneously represses transcription of genes preferentially expressed under acidic conditions (Tilburn et al ., ; Díez et al ., ). Han and colleagues () identified a pacC homologue, cmpacC , in C. minitans . Han and colleagues () also found that transcription of cmpacC as well as the two mycoparasitism‐associated genes cmch1 and cmg1 in C. minitans was increased in parallel when ambient pH increased from 3 to 8.…”
Section: Discussionmentioning
confidence: 99%
“…Han and colleagues () identified a pacC homologue, cmpacC , in C. minitans . Han and colleagues () also found that transcription of cmpacC as well as the two mycoparasitism‐associated genes cmch1 and cmg1 in C. minitans was increased in parallel when ambient pH increased from 3 to 8. Therefore, cmpacC may positively regulate transcription of Cmch1 and Cmg1 , but negatively regulate transcription of Cmoxdc1 , in C. minitans .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations